2006
DOI: 10.2355/isijinternational.46.614
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Melting of Some Slags in the Al2O3–CaO–MgO–SiO2 Quaternary System

Abstract: Ladle treatment plays increasingly important role in making clean steels nowadays. In many industrial practices, synthetic ladle slags are based on the Al 2 O 3 -CaO-MgOSiO 2 quaternary system. Usually, the compositions of the slags are targeted on the single liquid region of the phase diagram. On the other hand, the phase diagram information of the Al 2 O 3 -CaO-MgO-SiO 2 quaternary involves considerable uncertainties. The available sections of the phase diagrams in this system in Slag Atlas 1) are after Osbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 2 publications
1
10
0
1
Order By: Relevance
“…In addition, the pseudoternary sections reported as CaO-MgO-SiO 2 at fixed Al 2 O 3 or Al 2 O 3 -CaO-SiO 2 at fixed MgO cannot accurately predict the effect of MgO/Al 2 O 3 on liquidus temperature which is important for the current BF operations. It has also been demonstrated in recent studies that significant differences are observed for the phase diagrams in the Al 2 O 3 -CaOMgO-SiO 2 system between the new results [8][9][10][11][12] and those reported in the early research. [5][6][7] On the other hand, solid solutions presented in the system Al 2 O 3 -CaO-MgO-SiO 2 , in particular melilite phase in which industrial slags are operated, are important for optimisation of the thermodynamic database.…”
Section: Introductionsupporting
confidence: 51%
“…In addition, the pseudoternary sections reported as CaO-MgO-SiO 2 at fixed Al 2 O 3 or Al 2 O 3 -CaO-SiO 2 at fixed MgO cannot accurately predict the effect of MgO/Al 2 O 3 on liquidus temperature which is important for the current BF operations. It has also been demonstrated in recent studies that significant differences are observed for the phase diagrams in the Al 2 O 3 -CaOMgO-SiO 2 system between the new results [8][9][10][11][12] and those reported in the early research. [5][6][7] On the other hand, solid solutions presented in the system Al 2 O 3 -CaO-MgO-SiO 2 , in particular melilite phase in which industrial slags are operated, are important for optimisation of the thermodynamic database.…”
Section: Introductionsupporting
confidence: 51%
“…Some disagreements between experimental results and the phase diagram from Osborn et al [1] have been reported. [5] In a recent work by some of the current authors, [6] liquidus lines for 1773 K and 1873 K (1500°C and 1600°C) were determined experimentally in the 30 mass pct Al 2 O 3 section in the CaO-rich corner of the Al 2 O 3 -CaO-MgO-SiO 2 system. The results generally agreed well with the work by Osborn et al [1] with a few exceptions.…”
Section: The Oxide System Al 2 O 3 -Cao-mgo-sio 2 (Cmas)mentioning
confidence: 99%
“…[5] was evaluated to 188 in an previous work [6] at 1773 K (1500°C) under similar circumstances. This term is denoted by f 1773 K AlO 1:5 .…”
Section: Mgo Cao ð þ and Dg Xsmentioning
confidence: 99%
“…Esse sistema é adotado com frequência devido à sua alta compatibilidade com os refratários utilizados no refino secundário do aço na panela [4,5]. Geralmente, a composição das escórias do sistema CMAS (CaO-MgO-Al₂O₃-SiO₂) fica numa região líquida do diagrama de fase, mas esses diagramas encontrados na literatura apresentam muitas regiões incertas, que podem ser uma região de fase líquida ou múltiplas fases [4]. O que ocasiona divergências entre os resultados encontrados experimentalmente em comparação com a literatura.…”
Section: Introductionunclassified